2021
DOI: 10.1093/infdis/jiab398
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome of Healthy Vietnamese Adults and Children Is a Major Reservoir for Resistance Genes Against Critical Antimicrobials

Abstract: Antimicrobials are a key group of therapeutic agents. Given the animal/human population density and high antimicrobial consumption rate in Southeast Asia, the region is a focal area for monitoring antimicrobial resistance (AMR). Hypothesizing that the gastrointestinal tract of healthy individuals in Vietnam is a major source of AMR genes that may be transferred to pathogens, we performed shotgun metagenomic sequencing on fecal samples from 42 healthy Vietnamese people (21 children and 21 adults). We compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Nevertheless, our results are more or less comparable with the reported 764 gene ARG subtypes from neighbouring Singapore, which also observed the dominance of tetracycline and aminoglycoside resistance genes in urban wastewater 15 . Regardless of the observed quantity, the high diversity of ARGs observed in our cohort is aligned with other studies indicating the endemicity of antibiotic resistance in Southeast Asia 14 , 45 . In particular, the high prevalence of resistance genes against aminoglycosides, cephalosporins, macrolides, and fluoroquinolones is a significant concern, considering their status as critically important antimicrobials for the treatment of infectious diseases 46 .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Nevertheless, our results are more or less comparable with the reported 764 gene ARG subtypes from neighbouring Singapore, which also observed the dominance of tetracycline and aminoglycoside resistance genes in urban wastewater 15 . Regardless of the observed quantity, the high diversity of ARGs observed in our cohort is aligned with other studies indicating the endemicity of antibiotic resistance in Southeast Asia 14 , 45 . In particular, the high prevalence of resistance genes against aminoglycosides, cephalosporins, macrolides, and fluoroquinolones is a significant concern, considering their status as critically important antimicrobials for the treatment of infectious diseases 46 .…”
Section: Discussionsupporting
confidence: 91%
“…The high consumption frequency reported is aligned with a 2019 report suggesting the endemicity of antibiotic resistance in Southeast Asia 44 . Peering deeper into the region, Pereira-Dias et al (2021) 14 recently reported the gut resistome of 42 children and healthy adults from Vietnam, detecting 132 ARGs, which is much lower than the 1038 ARGs detected in this cohort. However, our study also utilized a much larger sample size ( n = 200 versus n = 42) and sequencing reads (mean ~26 million reads per subject versus 12 million reads).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…As with the gastrointestinal tract, the respiratory tract harbors diverse microbial communities acquired early during life [4][5][6] that are continually influenced over the lifespan by exposures to organisms from the environment and other humans, as well as to antimicrobials. The gut, respiratory tract, and other human anatomical microbiomes serve as reservoirs for ARGs, or antimicrobial resistomes, and act as potential sites of ARG acquisition and transmission 7 .…”
mentioning
confidence: 99%